Dr. Kongkrit Chaiyasate — Deep Plane Facelift — Bloomfield Hills - Chaiyasate, Kongkrit (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Kongkrit Chaiyasate, practicing in Bloomfield Hills, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-002985; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; bloomfield hills